THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING AND SELF-ESTEEM ON THE READING COMPREHENSION OF THE EIGHT GRADE STUDENTSâ OF SMPN 3 SUMBAWA - Wardiani, Hajaratul; SEKEN, KETUT; Artini, L. P. (Jurnal Pendidikan Bahasa Inggris, 2013)
Â Abstract Â This research was aimed at finding the effect of contextual teaching and learning upon studentsâ reading comprehension. Conducted at SMP 3 Sumbawa, it was experimental research with posttest only control group design of a factorial 2x2 type. The research variables were CTL as an independent variable, studentsâ reading comprehension as a dependent variable, and self-esteem as a moderator variable. Research instruments used to collect data were a reading comprehension test and a questionnaire on self-esteem. The population of the research was all students at the second grade. The research sample consisted of two classes each having 40 students. The research result shows that: 1) Contextual Teaching and Learning Method is more effective than conventional method in teaching reading comprehension (FA = 77.585 and p=0.00 <0.05); 2). Â The students having high self-esteem have better reading comprehension than those having low self-esteem (FB = 31.980 and p=0.00<0.05); and 3) there is no interaction between teaching methods and studentsâ self-esteem in teaching reading comprehension (FA = 1.439 and p=0.234 >0.05). Â Keywords: CTL, studentsâ reading comprehension, self-esteem